Pendidikan Karakter di Lingkungan Keluarga Selama Pembelajaran Jarak Jauh pada Masa Pandemi COVID-19 - I Putu Yoga Purandina; I Made Astra Winaya (Jayapangus Press, 2020)
COVID-19 provides a bad life for human life. All activities become inhibited and limited. Similarly in the field of education. Students must learn and do their activities at home. But this can be a good development for the development of the character of education in Family Environment. Thus the purpose of this research is to study whether research studies while at home are accompanied by parents who are able to develop character education, that is the first. Second, to find out what character values ​​can be developed during learning at home. Third, to find out the cause of developing with these character values. This study used qualitative research method. With case studies on kindergarten and elementary school students in Kecamatan Marga. Data obtained by distributing questionnaires to students, parents and teachers through the Whatsapp group of teachers and parents of students. Also strengthened by interview data on students, parents and teachers. The results showed differences in the development of character education and the relationship between children and parents that were quite good during learning from this house. Character values ​​that can be developed from activities carried out by students at home are (1) Religious, (2) Disciplinary, (3) Creative, (4) Independent, (5) Responsibility, and (6) Curiosity. The development of these character values ​​is the result of the synergy of teachers and parents in guiding students with gratitude, engaging, carrying out positive activities together in this COVID-19 pandemic.